Can the effects of using all suitable lags of an instrument comparable to that of an additional basic instrument in instrumental variable regression analysis of heteroskedastic linear models? - Yip, Chee Yin; Lim, Hock Eam; Hong, Pei Yee; Yip, Seng Joe (2010)
It is found that using all suitable lags of one instrument can increase the efficiency of finite sample IV estimator tremendously.The former is about 10% more efficient than the latter.The efficiency gains by using all suitable lags of one instrument is approximately about 1.1 times of what can be obtained by the inclusion of a similarly powerful instrument.